INTRODUCING INDONESIAN CRITICAL VIEWS FOR SOCIO-ENVIRONMENTAL ACCOUNTING STUDIES: INSIGHT FROM TAN MALAKA’S THOUGHT - Shahib, Habib Muhammad; Sukoharsono, Eko Ganis; Achsin, M.; Prihatiningtias, Yeney Widya (The International Journal of Accounting and Business Society, 2020)
Purpose  — This research tries to introduce one of the critical thoughts typical of Indonesia, namely Tan Malaka's view, which can be used in socio-environmental accounting studies.Design/methodology/approach  — This research uses a narrative literature review method, this article then compiles the Tan Malaka critical methodology pattern that focuses on the role of the government as a regulator, supervisor, and executor of socio-environmental issues to present an accountability framework for social-environmental issues to present an accountability framework for social-environmental issues.Findings  — This result of this research shows that the development of paradigmatic studies in the field of accounting opens up great opportunities to complement, refine and even present concepts to new accounting models that are in line with the demands of the times, as in this article shown, which borrows Tan Malaka's thoughts. This thought has a role as a methodological basis for presenting the concept of social-environmental accountability typical of Indonesia, which is strongly influenced by the active political movements of the elements of society.Practical Implications  — This research encourages the presence of socio-environmental accounting studies without forgetting the context of locality and the dynamic people's political aspirations.Originality/value  — In particular, the framework of this research is composed of the aspiration of people affected by socio-environmental problems that do the political movement, together with NGOs, to protest the socio-environmental issues.Keywords Socio-Environmental, Accounting, Critical, Methodology, Tan MalakaPaper Type Research Paper.